Rekontruksi Representasi Gaya Metode Kurikulum Pembelajaran di sekolah: Penelitian - Ulhaq, Daffa; Hakim, Azizul; Abdurrahmansyah, Abdurrahmansyah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Maintaining the arrangement and momentum of learning involves extensively using innovative methods that can serve as a foundation guiding educational sovereignty; it will never disappear, like oxygen floating in the air. Where improvements and development of the curriculum will adapt from era to era. It is not only through particles in confusing domains, but it focuses on educators and teachers being able to solve problems that provide solutions when consonance occurs in responding to the challenges of the era, which have become challenges for educators up to now. When collaboration is established between the performance of educators and teachers, it will facilitate the reconstruction of methods that the curriculum will determine, whether from the central or branch levels.